O Programa Cidadania na Mesa e a perspectiva dos direitos humanos - Silva, Williana Angelo da (2018)
This dissertation aims to analyze the possibility of operationalizing a human right, in the case of food, through the implementation of public social policy, demonstrating that to ensure continuity of said policy it is important that it is properly regulated. For this purpose, the Citizenship in the Table Program - PCM, elaborated and operationalized in the city of Sorocaba was taken as object of study. The PCM in its implementation was composed of three fronts of action: healthy cooking in motion, the green basket and the food voucher, the latter being the only one regulating by municipal law. The PCM analysis was theoretically subsidized by the bibliographical research around the concepts of human rights, public policies, public management, human right to adequate food, and food and nutritional security. Data collection was promoted through semi-structured interviews, focus group and documentary analysis, with a qualitative approach. As a result, it was possible to verify possible points of improvement, of recovery and positive points in terms of attending to the population. The profile of the program was also evidenced as an action in line with the food and nutrition security policy, which should have its own apparatus and should not be subordinated to a specific transversal policy. During the course of the research, through the exchange of municipal management and cuts promoted by the federal government, the 'green basket' action and 'healthy cooking in motion' were canceled and the families were no longer met, confirming the hypothesis that regulation in law is fundamental for guaranteeing the continuity of a program linked to a specific policy and overcoming the practice of government policies, which are sometimes replaced without due impact and feasibility analysis.